Development of Modul Based Character Education on Environmental Pollution’s Lesson for Class VII of Junior High School - Pasaribu, Hamidah; Ulfa, Syarifah Widya (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2022)
A module is a learning tool in written or printed form that contains learning materials for learning objectives, instructions for learning activities, and exercises that may be utilized on their own and are designed in a way that is both systematic and appealing in order to produce the desired skills and abilities. The intended output of this research is a printed character education module focused on environmental topics. This module's development followed a 4D model-based R&D process., namely definition, design, development, and deployment. Module validation is carried out by media and material expert lecturers, along with student response questionnaires. The test was conducted at SMP Karya Bunda Kab. Deli Serdang class VII with 28 students. The average results of media and material expert validation are 79.5%, and student response questionnaires with an average of 85%. The results showed that the character education-based module that was developed was included in the appropriate category for use, which was reviewed from the results of the validation by media and material experts, and the responses of students. Based on this, the developed module can be used in learning activities.